STRATEGI BERTAHAN BRAND "APPLE" DIMASA PANDEMI COVID19 DAN PENERAPANNYA PADA UMKM DI KOTA MALANG SEBAGAI UPAYA KEBERLANGSUNGAN USAHA - Dwi Dayanti Oktavia; Riyanto Setiawan Suharsono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research was conducted to find out the survival strategy used by Apple during the Covid-19 pandemic so that it can answer what MSME actors can do to be able to maintain their business in the midst of the Covid-19 Pandemic that hit the world. The research method used is the research method used in this study is a qualitative analysis with exploratory steps with participatory observation techniques. Sources of data used are primary data in the form of observations and secondary data in the form of data collected, processed and presented by other parties in the form of books and results of previous research related to MSMEs. Respondents or informants in this study are infinite. The results of this study indicate that the survival strategy carried out by the "Apple" Brand, namely innovation, can be applied to MSMEs in Malang City and has a very good impact on business continuity during the Covid 19 Pandemic Period.